Exploring the genetic diversity of Mediterranean fig trees highlights genes associated with fruit traits - Castellacci, Marco; Usai, Gabriele; Vangelisti, Alberto; Simoni, Samuel; Natali, Lucia; Mascagni, Flavia; Cavallini, Andrea; Lopez-Corrales, Margarita; Domínguez, Maria Guadalupe; Baraket, Ghada; Haffar, Sahar; Kuden, Ayzin; et al. (Frontiers in Plant Science, 2026)
The fig tree (Ficus carica L.) is a historically and economically important perennial crop in the Mediterranean region, valued for its fruit, leaves, and latex, which are employed in food, pharmaceutical, and cosmetic applications. Despite the agronomic and cultural relevance of Ficus carica, contemporary breeding programs are limited, and the genetic basis for major agro-morphological traits remains insufficiently characterised. To address this knowledge gap, we performed whole-genome resequencing on 286 genotypes from germplasm collections in Spain, Turkey, and Tunisia. Variant discovery identified 1,374,111 high-quality single nucleotide polymorphisms (SNPs), 2,448,766 small insertions/deletions, 218 copy number variants, and 1363 structural variants, many of which affect genes involved in stress responses, metabolism, signalling, and development. Population genomics revealed three main clusters corresponding to geographic origin, with some intermixing and cryptic relatedness reflecting historical germplasm exchange. By integrating genomic and phenotypic data, we identified 481 significant SNPs and candidate genes linked to 11 fruit traits and productive type, including genes associated with fruit weight (FMO1 and MYB transcription factors), fruit size (ABC transporters and WAK kinases), firmness (CML22 and sugar transporters ERD6s), sugar content and acidity (CYP94C1 and PPR proteins), and productive type (PP2C63). This study represents the most comprehensive genomic and phenotypic resource for F. carica to date, providing a robust foundation for germplasm management, marker-assisted selection, and breeding strategies, including the application of genome editing technologies to accelerate the improvement of fruit quality, yield, and adaptability.